Significance of intraoperative induced cough reflex in reducing the incidence of residual and recurrent lumbar disc herniation after microdiscectomy. A prospective cohort study - Mohamed Samir Abdelhamid; Tarek Anwar Elfiky; Hesham Aly El Saghir; Mahmoud Elsayed Ali Nafady; Yasser Mohamed Ehab Amin Elmansy (Alexandria Journal of Medicine)
Purpose The study objective was to evaluate the significance of the intraoperative induced cough reflex in detecting the hidden residual disc material that could be a cause of early postoperative recurrence.Literature overview Recurrent LDH after discectomy is a common problem (2% to 25%).Methods A prospective cohort included 70 consecutive patients who underwent single level lumbar microdiscectomy in the period between November 2021 and January 2023.The microdiscectomy procedure was performed in a standard way. After removal of the disc fragment, the test was started by lightening of the anesthesia and slight movement of the endotracheal tube following the reversal of the muscle relaxants. After the cough, the anesthesia is reinstituted, and repeat microscopic examination for unstable disc material was performed. The reflex was considered positive if there was an unstable disc fragment which was removed.Results A total of 70 patients were included in the study. Forty (57.1%) patients were males and 30 (42.9%) were females. The mean age was 39.45 ± 12.09 years (range: 17.0–72.0 years). The mean follow-up was 16.8 ± 7.8 months (range: 6–36 months). The reflex was positive in 10 patients (14.3%). Radiographic evidence of recurrence was encountered in nine patients (12.9%). However, only two patients out of 70 (2.85%) were symptomatic and were managed by PLIF.Conclusion The intraoperative induced cough reflex is a simple, safe and could be a useful method in an attempt to reduce the early symptomatic recurrence of LDH due to a residual unstable disc fragment after microdiscectomy.